Engineered protein elastomeric materials - Liu, Zhongcheng (2024)
Natural evolution endows some insects and marine organisms with a special class of protein-based elastic tissues that possess energy feedback characteristics, providing them with the foundation for jumping and flying, and protecting them from the damage caused by movements or waves. However, the design and fabrication of such protein-based elastomeric materials that can function in human society through biomimetic strategies still remains challenging. Recombinant proteins designed by synthetic biology can mimic the advantageous structures in natural proteins and can be biosynthesized without the requirements for harsh conditions such as high temperatures and cytotoxic agents, which provides a great opportunity to prepare protein-based elastomeric materials. In this review, starting from the design of protein molecules, we highlight an overview of the synthesis of elastomeric materials based on recombinant resilin, recombinant elastin-like proteins and other recombinant folded proteins, etc., and then demonstrate their application progress in the fields of biomedicine and high technology. Finally, the challenges and prospects for the future development of protein-based elastomeric materials are envisioned to provide insights into the design and synthesis of the next generation of protein-based elastomeric materials.